Multi‐Peer Disagreement and the Preface Paradox. (3rd September 2014) - Boyce, Kenneth; Hazlett, Allan
Abstract: The problem of multi‐peer disagreement concerns the reasonable response to a situation in which you believe P1 … Pn and disagree with a group of 'epistemic peers' of yours, who believe ∼P1 … ∼Pn, respectively. However, the problem of multi‐peer disagreement is a variant on the preface paradox; because of this the problem poses no challenge to the so‐called 'steadfast view' in the epistemology of disagreement, on which it is sometimes reasonable to believe P in the face of peer disagreement about P. After some terminology is defined (§1), Peter van Inwagen's challenge to the steadfast view will be presented (§2). The preface paradox will then be presented and diagnosed (§3), and it will be argued that van Inwagen's challenge relies on the same principle that generates the preface paradox (§4). The reasonable response to multi‐peer disagreement will be discussed (§5), and an objection addressed (§6).